Cambodia in 2018: requiem for multiparty politics - Croissant, Aurel (Asian survey, 2019)
In 2018, ever-incumbent Prime Minister Hun Sen scored a landslide victory in the Cambodian general elections. Three factors in particular explain this outcome. First, the elimination of the main opposition party, whose strategy of a peaceful election boycott failed. Second, favorable economic conditions and government handouts of spoils to constituencies that traditionally supported the opposition. Third, the weak leverage of the United States and the EU, and the Hun Sen regime's strong links with China.
Gesehen am 13.12.2019
Keywords: Kambodscha